Systematic review with meta‐analysis: effectiveness of direct‐acting antiviral treatment for hepatitis C in patients with hepatocellular carcinoma. Issue 1 (6th December 2019) - He, Sichan; Lockart, Ian; Alavi, Maryam; Danta, Mark; Hajarizadeh, Behzad; Dore, Gregory J.
Summary: Background: Direct‐acting antiviral (DAA) therapy for hepatitis C virus (HCV) infection is highly curative and tolerable. Among patients with hepatocellular carcinoma (HCC), optimal timing of DAA therapy remains unclear. Data on efficacy of DAA therapy in patients with HCC would inform this decision‐making. Aim: To evaluate response to DAA therapy among patients diagnosed with HCV infection and HCC. Methods: Bibliographic databases and conference abstracts were searched. Meta‐analysis was conducted to pool sustained virologic response (SVR) estimates. Results: Fifty‐six studies with 5522 patients with HCV and HCC were included. Overall SVR was 88.3% (95% CI 86.1‐90.4). Twenty‐seven studies included patients with prior or present HCC (n = 3126) and patients without HCC (n = 49 138), in which SVR was 88.2% (95% CI 85.0‐91.4) and 92.4% (95% CI 91.1‐93.7) among patients with and without HCC, respectively (odds ratio: 0.54, 95% CI 0.43‐0.68, P < .001). In the subgroup analyses, higher SVR was seen in patients who received curative HCC management (SVR 90.4%, 95% CI 88.3‐92.4), or treated with sofosbuvir + NS5A inhibitor DAAs (SVR 96.9%, 95% CI 94.3‐99.4), or in patients with HCV genotype 1 infection (SVR 92.0%, 95% CI 88.1‐95.6). Conclusion: Response to DAA therapy was lower in patients with HCC compared to those without HCC, regardless of cirrhosis status. Among HCC patients, there was an impact of proportion with curative HCC management on DAA therapy response.